ANALYSIS OF THE PERFORMANCES OF THE 2024 OLYMPIC CHAMPION IN FREESTYLE WRESTLING IN THE CATEGORY UP TO 57 KG - Pavlov Ya.E.; Kolodeznikov K.S.; Uvarov M.V.; Nikitin A.S. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to analyze the competitive activity of freestyle wrestler Rei Higuchi. Methods and structure of the study. Pedagogical studies of competitive activity have been carried out, as well as an analysis of video recordings of freestyle wrestlers based on the results of their participation in the Olympic tournament in Paris. Results and conclusions. A study of wrestler Ray Higuchi’s competitive practice revealed that at the 2024 Olympic Games he was active in the stand 63.6% of the time, and in the stalls 36.3%. At the same time, his arsenal of technical actions was mainly reduced to 2-3 techniques. Despite the limited set of techniques, Higuchi is highly effective in applying proven combinations, varying them during the match. Key techniques include a side pass with a switch to the other side when an opponent resists, or a transfer to the left hand with a pass to the right side leg, a two-leg pass, as well as deceptive maneuvers preceding a technical action. Characteristic features of the Higuchi style are: disorientation of the opponent due to sudden movements in different directions, a stable stance, active work with the hands to prevent seizures and head control, as well as dominance in determining the pace and nature of the fight. The information about technical actions obtained as a result of the analysis forms a valuable methodological database that can assist coaches and athletes in optimizing the training process.